Global methyl halide emissions from biomass burning during 2003–2021 - Xiaoyi Hu; Di Chen; Liting Hu; Bowei Li; Xinhe Li; Xuekun Fang (Environmental Science and Ecotechnology, 2023)
Methyl halides (CH3Cl, CH3Br, and CH3I) are ozone-depleting substances. Biomass burning (BB) is an important source of methyl halides. The temporal variations and global spatial distribution of BB methyl halide emissions are unclear. Thus, global methyl halide emissions from BB during 2003–2021 were estimated based on satellite data. A significant decreasing trend (p < 0.01) in global methyl halide emissions from BB was found between 2003 and 2021, with CH3Cl emissions decreasing from 302 to 220 Gg yr−1, CH3Br emissions decreasing from 16.5 to 11.7 Gg yr−1, and CH3I emissions decreasing from 8.9 to 6.1 Gg yr−1. From a latitudinal perspective, the northern high-latitude region (60–90° N) was the only latitude zone with significant increases in BB methyl halide emissions (p < 0.01). Based on an analysis of the drivers of BB methyl halide emissions, emissions from cropland, grassland, and shrubland fires were more correlated with the burned area, while BB emissions from forest fires were more correlated with the emissions per unit burned area. The non-BB emissions of CH3Cl increased from 4749 Gg yr−1 in 2003 to 4882 Gg yr−1 in 2020, while those of CH3Br decreased from 136 Gg yr−1 in 2003 to 118 Gg yr−1 in 2020 (global total CH3I emissions are not available). The finding indicates that global CH3Cl and CH3Br emissions from sources besides BB increased and decreased during 2003–2020. Based on our findings, not only searching for unknown sources is important, but also re-evaluating known sources is necessary for addressing methyl halide emissions.